Mechanical behaviour of fly-ash-treated expansive soil. Issue 1 (19th February 2018) - Mir, Bashir A.; Sridharan, Asuri
Abstract : A major source of electrical energy is thermal power, which results in large quantities of coal ashes. Fly ash, which is produced from the combustion of pulverised coal, has an important place among industrial by-products. Currently, in India, more than 180 Mt of fly ash is being generated annually, posing the dual problem of environmental pollution and difficulty in disposal. This calls for establishing strategies to use the product as an engineered construction material in geotechnical applications for which the mechanical behaviour of soil–fly-ash mixes is an important consideration. In this study, high-calcium (class C) and low-calcium (class F) fly ashes in different proportions by weight were added to expansive soil to evaluate the effect of fly ashes on the strength behaviour of soil–fly-ash mixtures. Compacted clay–fly-ash samples were cured for 7 and 28 d and subjected to unconfined compression tests. It was found that 20% of class C fly ash is the optimum quantity to improve the characteristics of expansive soil, compared with 60% of class F fly ash. The main objective of the study was to illustrate the beneficial effects of fly ashes on the mechanical behaviour of fly-ash-treated expansive soil.